Emotional intelligence in sport and exercise: A systematic review - Laborde, S.; Dosseville, F.; Allen, M. S. (Scandinavian Journal of Medicine & Science in Sports, 2016)
This review targets emotional intelligence (EI) in sport and physical activity. We systematically review the available literature and offer a sound theoretical integration of differing EI perspectives (the tripartite model of EI) before considering applied practice in the form of EI training. Our review identified 36 studies assessing EI in an athletic or physical activity context. EI has most often been conceptualized as a trait. In the context of sport performance, we found that EI relates to emotions, physiological stress responses, successful psychological skill usage, and more successful athletic performance. In the context of physical activity, we found that trait EI relates to physical activity levels and positive attitudes toward physical activity. There was a shortage of research into the EI of coaches, officials, and spectators, non-adult samples, and longitudinal and experimental methods. The tripartite model proposes that EI operates on three levels - knowledge, ability, and trait - and predicts an interplay between the different levels of EI. We present this framework as a promising alternative to trait and ability EI conceptualizations that can guide applied research and professional practice. Further research into EI training, measurement validation and cultural diversity is recommended.